A Qualitative Comparative Study of Storytelling Through the Thematic Apperception Test Among Two Young Adults with a History of Substance Abuse in a Selected De-Addiction Centre in Delhi, India - Anjali Samson (International Journal of Evidence Based Nursing And Practices, 2026)
Introduction: Substance use can deeply affect an individual’s personality, relationships, and psychological functioning. The thematic apperception test (TAT), a projective psychological tool, helps uncover unconscious thoughts and emotions through storytelling. Objective: (i) To explore and compare the underlying personality dynamics of two young adult males with a history of substance use through TAT card analysis. Method: A qualitative comparative case study design was used. Ten standard TAT cards were presented to each participant, both with a known history of substance use. Participants narrated stories based on the cards. Narratives were thematically analyzed to identify psychological themes, emotions, and defense mechanisms. Results: Subject A (cannabis user) showed optimistic, imaginative stories with themes of ambition and independence, using denial and rationalization as defense mechanisms. Subject B (opioid user) revealed stories filled with guilt, rejection, and helplessness, showing signs of emotional distress and withdrawal defenses. Conclusion: TAT is a useful tool for exploring the inner emotional world of individuals with substance use histories. The contrasting storytelling patterns reflect different coping styles and personality profiles, providing insight into psychological support and therapeutic interventions.
Keywords: TAT; personality assessment; projective test; psychology; storytelling; substance use